2021
DOI: 10.1097/scs.0000000000008436
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Studies in Facial Reanimation Surgery: Consensus and Controversies in the Top 50 Most Cited Articles

Abstract: Facial paralysis can impair one's ability to form facial expressions that are congruent with internal emotion. This hinders communication and the cognitive processing of emotional experience. Facial reanimation surgery, which aims to restore full facial expressivity is a relatively recent undertaking which is still evolving. Due in large part to published techniques, refinements, and clinical outcomes in the scientific literature, consensus on best practice is gradually emerging, whereas controversies still ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…The facial muscle control of the facial nerve allows us to communicate our joys and sorrows through micro-expressions, which are essential in our daily lives, and thus patients are highly motivated to treat facial nerve injuries once they occur. 21 Regaining the facial neural control over the muscles of expression is the highest priority in our treatment. With the deepening of research, it has been found that early tension-free anastomosis can achieve the best therapeutic effect when conditions permit, but such literature reports are few.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The facial muscle control of the facial nerve allows us to communicate our joys and sorrows through micro-expressions, which are essential in our daily lives, and thus patients are highly motivated to treat facial nerve injuries once they occur. 21 Regaining the facial neural control over the muscles of expression is the highest priority in our treatment. With the deepening of research, it has been found that early tension-free anastomosis can achieve the best therapeutic effect when conditions permit, but such literature reports are few.…”
Section: Discussionmentioning
confidence: 99%
“…The facial muscle control of the facial nerve allows us to communicate our joys and sorrows through micro-expressions, which are essential in our daily lives, and thus patients are highly motivated to treat facial nerve injuries once they occur 21 . Regaining the facial neural control over the muscles of expression is the highest priority in our treatment.…”
Section: Discussionmentioning
confidence: 99%